Building a successful social venture : a guide for social entrepreneurs - Carlson, Eric Daniel, 1944-; Koch, James L., 1944- (Oakland, Berrett-Koehler Publishers, Inc., 2018)
"While social entrepreneurship is a rapidly growing field and thousands of social ventures start each year, the tools and processes that work on the ground are missing from most textbooks. This book will function both as a text for graduate-level students and a business planning guide for practitioners"--
Top-down and bottom-up theories of social progress -- The market at the base of the pyramid -- Paradigms for social venture business plans -- Mission, opportunity, strategies -- The external environment -- The target market segment -- Operations and value chain -- Organization and human resources -- Business model -- Metrics & accountability -- Operating plan -- Financing -- The path forward.
Includes bibliographical references and index.
Keywords: Social entrepreneurship -- Textbooks; Strategic planning -- Textbooks